An Analytical Study of Reproduction of Reality in Cinema - Alirezaei, Ehsan (Journal of Ecohumanism, 2025)
The representation system was developed based on Plato’s words in the seventh chapter of the Republic, according to which simulacra are copies of reality. The representation of reality or the nature of the image-reality relationship, has always been an essential topic of study in the philosophy of art. The mechanical recording and reproduction of the world by the camera in the modern era is the turning point in the representation of reality, ultimately leading to the collapse of the representation system. This study investigates the image-reality relationship using a descriptive-analytical approach to identify the relationship of cinematic images with reality. It first discusses the Realism in Film Theory centered on Andre Bazin and then Jean Baudrillard’s thoughts on Hyperreality in postmodernism. The study shows that Realism in Film Theory has also addressed the problem of the representation of reality in cinema within the framework of the traditional concept of representation and based on the principle of referring images to external reality. However, by questioning the idea of representation in postmodernism and analyzing the process of separating reality from its visual signs, Baudrillard offers a new reading of the image-reality relationship.